Mamalia Kecil Terestrial di Gunung Singgalang, Sumatera Barat - Inda Dwi Solina; Wilson Novarino; - Rizaldi (Jurnal Biologi Universitas Andalas, 2013)
Mt. Singgalang have high diversity of flora and fauna, which also drives the high diversity of small terrestrial mammals. A study on diversity of small terrestrial mammals (Muridae, Erinaceidae and Soricidae) has been caried out from July to August 2012 by using an extensive trapping method. This research used 30 snap traps and 10 20L pit fall trap drift fences in 360 trap-nights. Fourty individu of small terrestrial mammals have been caught, belong to six genera, three families and two orders. Those species were Hylomys suillus, Crocidura beccarii, Crocidura neglecta, Leopoldamys sabanus, Maxomys hylomyoides, Maxomys surifer, Niviventer rapit, and Sundamys infraluteus. Pit fall trap drift fences was more effective method to trap Crocidura spp.Keywords: species identification, small terrestrial mammals, Mt.Singgalang